THE EFFECT OF FINANCIAL LEVERAGE ON FINANCIAL PROFITABILITY: A STUDY OF NON-FINANCIAL INSTITUTIONS LISTED ON THE INDONESIAN STOCK EXCHANGE - Sirait, Eugenia Chacita; Pangestuti, Irene Rini Demi (Institut Teknologi dan Ilmu Sosial Khatulistiwa, 2026)
This study aims to reveal the effect of Financial Leverage on Financial Profitability in non-financial companies listed on the Indonesia Stock Exchange. The population of this study is non-financial companies listed on the Indonesia Stock Exchange that attach their financial reports publicly from 2018-2023. The data used in this study comes from Bloomberg data from the Faculty of Economics and Business, Diponegoro University, Semarang. The number of samples based on the purposive sampling method is 68 companies and with a sample of 408. The analysis in this study is multiple linear regression analysis using IBM SPSS 25. The findings in this study indicate that Equity Multiplier, Interest Coverage ratio, Degree of Financial Leverage, have no effect on ROA and ROE, Fixed Charge Coverage ratio and Capitalization Ratio have a positive effect on ROA and ROE, Debt to EBITDA has a negative effect on ROA and ROE. Keywords: Financial Leverage, Profitability, Indonesia Stock Exchange